Pulse Resonance Active-Power Amplifier. Offer and Justification of Workability (Global Journals of Research in Engineering, 2023)
Actuality Expert assessments of the growing demand for energy resources convincingly presented by numerous works of the international organization International Energy Agency and discussed at relevant world-class forums emphasize the development of the electric power industry as a necessary and relevant condition for successfully solving the problems of modern scientific and technological progress Purpose The purpose of the work is to propose and justify the workability of a pulsed resonant amplifier of active electric power consisting of two series contours with common capacitive energy storage including analysis and numerical assessments of the main characteristics of ongoing electromagnetic processes Formulation of the Problem This work was initiated by the current energetics needs due to the depletion of natural resources and the rapidly growing needs of the world economy Methodology When deriving the main analytical relationships to justify the fundamental possibility of resonant amplification of active electric power it turned out to be sufficient to confine ourselves to the proposal and study of an amplifier circuit with a single excitation of a current pulse in the load The mathematical apparatus of research is a set of provisions and methods for calculating transient processes in electrical circuits with active-reactive elements Novelty For the first time with a theoretical and experimental justification of the workability a circuit of a pulsed amplifier of the active electrical power of a harmonic signal was proposed consisting of two series contours with common capacitive storage The first of them is a reactive power amplifier and the second is a converter of reactive power into active power released when the excited current flows in any electrical load Main Results With the justification of capacity a circuit of a pulsed resonant active electric power amplifier is proposed consisting of two series circuits with common capacitive energy storage Analytical dependencies are obtained for the main characteristics of the ongoing electromagnetic processes and it is shown that the phenomenon of voltage resonance allows one to achieve an increase by more than an order of magnitude in the active power of a harmonic voltage source Based on the analysis numerical estimates and experimental testing the workability of the proposed circuit of a pulsed resonant amplifier of active electric power is substantiated Practical Significance A method for resonant amplification of the active electric power of harmonic signals is proposed On a practical example indicating the specific values of the circuit elements its workability is illustrated The results obtained can be used as the basis of a real technical device for obtaining resonant electrical energy from the surrounding space
Keywords: harmonic signals; series circuits; voltage resonance; pulse mode; active electric power amplification